First and second generation immigrant educational attainment and labor market outcomes: a comparison of the United States and Canada - Abdurrahman Aydemir; Arthur Sweetman (Institute for the Study of Labor (IZA), 2006)
The educational and labor market outcomes of the first, first-and-a-half, second and third generations of immigrants to the United States and Canada are compared. These countries' immigration flows have large differences in source countries, scale and timing, and Canada has a much larger policy emphasis on skilled workers. Following from these, the educational attainment of US immigrants is currently lower than that in Canada and the intergenerational transmission of education is expected to cause the gap to grow. This in turn influences earnings. Controlling only for age, the current US second generation has earnings comparable to those of the third, while earnings are higher for the second generation in Canada. Interestingly, the positive wage gap in favour of first-and-a-half and second generation immigrants in Canada is exceeded by the gap in educational attainment, but a lower immigrant rate of return attenuates education's impact. Moreover, observable characteristics explain little of the difference in earnings outcomes across generations in the US but their introduction into an earnings equation causes the Canadian second generation premium to switch signs and become negative relative to the third
Keywords: 330